A randomized controlled trial of laser-assisted ICSI. Issue 12 (30th September 2020) - Fawzy, Mohamed; Emad, Mai; Mahran, Ali; Abdelrahman, Mohamed Y; Fetih, Ahmed N; Abdelghafar, Hazem; Elsuity, Mohamed A; Rashed, Hend; Sabry, Mohamed
Abstract: STUDY QUESTION: Does the use of a laser to open the zona pellucida during ICSI (laser assisted or LA-ICSI) improve oocyte survival, embryo development and clinical outcomes? SUMMARY ANSWER: Compared to conventional ICSI, LA-ICSI increased rates of oocyte survival and some aspects of embryo development but it did not alter the ongoing pregnancy rate; after adjusting for oocyte survival, there was no beneficial effect of LA-ICSI on embryo development and utilization. WHAT IS KNOWN ALREADY: Oocyte degeneration occurs in a 10th of mature oocytes after ICSI. Pilot studies suggest that LA-ICSI may improve oocyte survivability. STUDY DESIGN, SIZE, DURATION: In a randomized controlled trial, 966 couples (16 122 metaphase II oocytes) were allocated to receive LA-ICSI (intervention) or conventional ICSI (control) between 17 September 2018 and 5 August 2019. Oocyte survival (primary endpoint), embryo development and ongoing pregnancy rates were compared. PARTICIPANTS/MATERIALS, SETTING, METHODS: Couples included in this study were recommended for ICSI due to female or male factor, unexplained infertility or a combination of factors. Patients were ineligible to participate in the study if they had uterine abnormality including thin endometrium, recurrent pregnancy loss, endometriosis or a severe medical condition. Concealed randomization to LA-ICSI or conventional ICSI, allocated in a 1:1 ratio, took place on stimulation Day 1 with replacement of blastocysts on only Day 5. The primary endpoint was oocyte survival with membrane integrity 24 h after the ICSI procedure. The sample size was estimated to detect a 3% increase in oocyte survival after LA-ICSI with 99% power at a 1% significance level. This also permitted the detection of 10% increase in ongoing pregnancy rate after LA-ICSI with 85% power at 5% alpha level. We used Poisson regression with zero-inflation for count data to estimate relative risk (RR) with 95% CI and logistic regression for clinical outcomes to estimate odds ratio (OR) with 95% CI. Both models adjusted for age as a covariate. MAIN RESULTS AND THE ROLE OF CHANCE: Compared with conventional ICSI, LA-ICSI resulted in a higher number of surviving oocytes (RR 1.08, 95% CI 1.05–1.12, P  < 0.001), as well as a higher number of fertilized oocytes (RR 1.08, 95% CI 1.04–1.13, P  < 0.001) and utilizable blastocysts (RR 1.09, 95% CI 1.04–1.15, P  < 0.001). Sensitivity analyses adjusted for oocyte survival showed no between-group difference in utilizable blastocysts (OR 1.01, 95% CI 0.95–1.08, P  = 0.73) and by calculating the mean rate, a reduction in utilizable blastocysts was shown (RR 0.95, 95% CI 0.94–0.97, P  < 0.001). Ongoing pregnancy showed no between-group difference (LA-ICSI 179/489 (37%) vs ICSI 201/477 (42%), OR 0.79, 95% CI 0.61–1.03, P  = 0.09). LIMITATIONS, REASONS FOR CAUTION: It was not possible to blind the embryologists involved in the ICSI procedure. However, there was concealment of randomization and blinding of outcome assessments reducing the risk of selection and measurement bias. WIDER IMPLICATIONS OF THE FINDINGS: A beneficial effect of LA-ICSI on oocyte survival should be shown to improve clinical outcomes, before its use in clinical practice is justified. STUDY FUNDING/COMPETING INTEREST(S): The study received no funding, and the authors declare that there are no conflicts of interest. TRIAL REGISTRATION NUMBER: NCT03665103 TRIAL REGISTRATION DATE: 11 September 2018 DATE OF FIRST PATIENT'S ENROLMENT: 17 September 2018